Motivational Techniques and LearnersaAcademic Achievement at Primary Level (Global Journal of Human-Social Science, 2013)
Motivation is significant to arouse students interest towards learning process in every teaching learning situation At primary level motivation plays important role as compared to the other levels of learning due to the fact that young learners need to be motivated towards learning as they experience the new knowledge Present study is designed to explore the impact of teachers motivational techniques on students academic achievements Here motivational techniques used by the primary school teachers were measured in relation with the academic achievement of primary school students In this research various objectives hypotheses and research questions were formulated The stratified random sampling technique was used to collect data from respondent teaching at Islamabad Model colleges Schools Sample size was based on 100 teachers 50 teachers were taken from five boys schools and 50 teachers were taken from five girls schools